PERSEPSI MASYARAKAT TERHADAP KINERJA APARATUR DESA NGADIREJO KECAMATAN SALAMAN KABUPATEN MAGELANG - Siregar, Paulina; Sri Sulistowati (PPM Sdirjianbang Akademi Militer, 2023)
Research on people's perceptions is needed as a way that can be used to control and evaluate the performance of village officials. The method used in this study is qualitative with data sources through interviews conducted with village heads, village officials, community leaders, religious leaders and the people of Ngadirejo Village. The results of this study are first, the perception of the Ngadirejo village community towards apparatus performance is more influenced by the characteristics of people who respond to stimuli and experiences from the community when services are provided from village apparatus. details of the problems that exist in the community from the old village apparatus, lack of work ethic of village government officials/equipment, not yet available good computers and printers are not available, lack of office transportation, low human resources lack of irrigation that functions properly, finance village which is still very lacking. Meanwhile, what comes from the opinion of the community is that there is an internal conflict between village officials, not being on time in carrying out their duties, village officials lack discipline in carrying out their duties, lack of responsibility and sincerity in carrying out their duties. Third, the driving factor for the performance of village officials is young people. and productive people in Ngadirejo village, fertile land, there is training from the government to the community